Disparities in Stunting Prevalence in Central Sulawesi: A Comparative Analysis of Determinants and Interventions in Two Districts - Amsal, Amsal; Hafid, Fahmi; Zainul, Zainul (Journal of Health and Nutrition Research, 2025)
Stunting among children under two years old remains a major public health issue in Indonesia, particularly in Central Sulawesi, where the 2024 prevalence reached 26.1%, exceeding the national rate of 19.8%. This study aimed to analyze disparities in stunting determinants and identify effective innovations for reduction using an ecological analytic design combining quantitative and qualitative approaches. Data were derived from the 2024 Indonesian Nutritional Status Survey (SSGI), district stunting dashboards, and in-depth interviews with key stakeholders in Sigi District (high prevalence, 33.0%) and Tojo Una-Una District (low prevalence, 16.5%). Results showed that stunting in Sigi was associated with limited access to health services, low immunization coverage, poor sanitation, low maternal education, minimal funding for specific programs (1.33%), and post-disaster challenges. In contrast, Tojo Una-Una achieved >90% essential service coverage, strong family mentoring by Family Assistance Teams (TPK), and adequate program allocation (15.03%) through innovations such as the Dapur Sehat Atasi Stunting (DASHAT) program and mobile clinics. Effective stunting reduction requires integrating specific nutrition actions with sensitive interventions addressing sanitation, education, and economic empowerment. Strengthening cross-sectoral collaboration, digital data monitoring (e-PPGBM), and replication of Tojo Una-Una’s best practices are critical to achieving the 2024 RPJMN target and supporting the 2030 Sustainable Development Goals